Enhancement in behavioral properties of cement mortar cubes admixed with reduced graphene oxide. (March 2020) - Prabavathy, S.; Jeyasubramanian, K.; Prasanth, S.; Hikku, G.S.; Robert, R.B. Jeen
Abstract: In this paper, we detail the enhancement in most of the prominent characteristics of cement mortar cubes fabricated by admixing with reduced graphene oxide (rGO) as an additive to a standard mix design. After curing the fabricated cement mortar cubes for 28 days, 0.1% rGO impregnated cement mortar cubes (0.1% rGOCMC) display higher compressive strength of 36.23 MPa in contrast to all other specimens (0.05%, 0.15% and 0.2%). Besides compressive strength, tests for water absorption, ultrasonic pulse velocity, carbonation, fire resistance, and acid attack further validate the superior performance of 0.1% rGOCMC over control mortar cubes. From all the obtained results, it is clear that 0.1% rGOCMC has the best characteristics of cement mortar to protect embedded metal reinforcement from corrosion and can be used as an effective structural material in the building industry. Graphical abstract: Image 1 Highlights: Cement mortar cubes are fabricated by admixing rGO as additive to standard mix design. 0.1% rGO impregnated cube displays higher compressive strength of 36.23 MPa. Better performance in tests like water absorption, UPV, carbonation, fire resistance, etc. 0.1% rGO impregnated cement is an effective material for the future building industry.